2021
DOI: 10.1111/1751-7915.13997
|View full text |Cite
|
Sign up to set email alerts
|

Can a combination of vaccination and face mask wearing contain the COVID‐19 pandemic?

Abstract: Summary The COVID‐19 pandemic is going into its third year with Europe again being the focus of major epidemic activity. The present review tries to answer the question whether one can come to grip with the pandemic by a combination of vaccinations and non‐pharmaceutical interventions (NPIs). Several COVID‐19 vaccines are of remarkable efficacy and achieve high protection rates against symptomatic disease, especially severe disease, but mathematical models suggest that the current vaccination covera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 97 publications
1
40
0
Order By: Relevance
“…Wearing masks even with complete vaccination is urgent and necessary and need to be clubbed with the non-pharmaceutical interventions to curb the pandemic. Many mathematical models are suggesting that current vaccination rate is not sufficient to fully prevent the spread of virus ( Brüssow and Zuber, 2021 ). It was reported that the Omicron variant (B.1.1.529) was found in an asymptomatic, fully vaccinated traveller in a quarantined hotel in Hong Kong, China, and had been transmitted to another fully vaccinated traveller staying in a room across the corridor from the index patient, indicating transmission of this virus variant despite strict quarantine precautions ( Gu et al, 2021 ).…”
Section: What Can Be Done In the Present Scenario?mentioning
confidence: 99%
“…Wearing masks even with complete vaccination is urgent and necessary and need to be clubbed with the non-pharmaceutical interventions to curb the pandemic. Many mathematical models are suggesting that current vaccination rate is not sufficient to fully prevent the spread of virus ( Brüssow and Zuber, 2021 ). It was reported that the Omicron variant (B.1.1.529) was found in an asymptomatic, fully vaccinated traveller in a quarantined hotel in Hong Kong, China, and had been transmitted to another fully vaccinated traveller staying in a room across the corridor from the index patient, indicating transmission of this virus variant despite strict quarantine precautions ( Gu et al, 2021 ).…”
Section: What Can Be Done In the Present Scenario?mentioning
confidence: 99%
“…In addition to vaccination, other recommended infection prevention measures include preventing contact with infected persons by maintaining a physical distance, thorough hand washing, and proper wearing of masks [12][13][14][15]. In particular, wearing masks has been found to significantly reduce COVID-19, and a synergistic effect is expected when combined with vaccination [12].…”
Section: Introductionmentioning
confidence: 99%
“…Vaccinated people had less risk of individual symptoms, severe disease, hospital admission, and death ( 44 ). The combination of vaccination and wearing a mask is potentially synergistic and is of high benefit in the prevention and control of COVID-19 ( 45 ).…”
Section: Discussionmentioning
confidence: 99%